Deteksi dan Karakterisasi Penyakit Bunt pada Biji Gandum Konsumsi Impor - Yuliawati; Wiyono, Suryo; Wahyu, Bonny Poernomo (Jurnal Fitopatologi Indonesia, 2022)
Detection and Characterization of Bunt Diseases in Imported Wheat Seed for FoodBunt is an important disease of wheat (Triticum aestivum) caused by the fungus Tilletia spp. This disease is a major concern in international trade because it can reduce the quality and quantity of wheat. Tilletia spp. is one of the quarantine pests that has not been found in Indonesia. This study was aimed to detect and characterize bunt disease in imported wheat seeds and testing its viability. The study began with taking samples from ships, describing disease symptoms, detection and identification of Tilletia spp. morphologically by washing test followed by teliospore viability test, temperature observation and grain or bran sampling at the wheat dan bran processing plant. The presence of the fungus Tilletia spp. is detected by looking for the symptoms which are characterized by brown to black seeds on part to the entire surface of the seeds, the seeds become stunted and showed malformations. Morphology identification confirmed the presence of the fungus T. laevis. Tilletia laevis did not germinate at all temperatures tested. The observed temperature at the wheat grain processing plant was between 48.5 ℃ and 94.0 ℃, while in the bran processing machine was 48.6 ℃ and 66.1 ℃. Teliospores of T. laevis was found in wheat samples but not in bran samples.